Mechanism of development of personnel-social strategies of management by personnel of tourism enterprises - Vadim Yarovyi (Економічний вісник університету, 2018)
The subject of the study is to determine the mechanisms of development of personnel and social strategies and the peculiarities of their implementation in the process of managing the development of tourism enterprises. The purpose of the work is to develop theoretical and methodological principles and recommendations for the formation of conceptual measures for the implementation of personnel and social strategies of tourist enterprises. Methodological basis of the article became general scientific and special methods of scientific knowledge, logical generalization and abstraction, structural analysis, method of comparative analysis, historical and other methods of research. Results of work. It is determined that special significance in the management system of tourism enterprises is given to the human factor, which is of fundamental importance for ensuring efficient and competitive activity of enterprises in a market economy. Therefore, personnel management is a multi-faceted and extremely complex process characterized by its specific features and regularities. Strategic approach to ensuring the effectiveness of personnel policy involves the development and implementation of personnel and social strategies that have a direct impact on the overall state of the enterprise, the formation of high-quality human resources, ensuring its development and effective use. The field of application of results. The results of the study can be used to improve the process of personnel management and to formulate measures to increase the effectiveness of the personnel policy of tourism enterprises. They are important for the management, systematic management of tactical and strategic activities of enterprises as a whole, as well as by structural subdivisions. Conclusions. The proposed human resources and social strategies of the tourist enterprise are a progressive approach to personnel management at the strategic level allowing to take into account the needs of the enterprise in personnel, depending on the level of business development, the environment and the market situation of tourist services.